2005
DOI: 10.1074/jbc.m411727200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the Insulin Receptor in Mouse Insulinoma (MIN6) Cells Reveals Multiple Roles of Insulin Signaling in Gene Expression, Proliferation, Insulin Content, and Secretion

Abstract: The role of insulin signaling in pancreatic ␤ cells has become increasingly apparent. Stably transformed insulinoma cell lines (MIN6) were created with small interfering RNA resulting in the reduction of insulin receptor (IR) expression up to 80% (insulin receptor knockdown, IRKD⌬80). Functionally perturbed IR signaling was confirmed with the absence of insulin-stimulated insulin receptor substrate 1 tyrosine phosphorylation. Additionally, Akt phosphorylation was reduced and responded poorly to glucose stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 63 publications
6
72
1
1
Order By: Relevance
“…Our preceding studies documented that glucose activated Akt through an autocrine/paracrine effect of insulin with subsequent activation of the PI3K pathway [26,28]. To extend these observations, we sought to test whether changes in glucose could regulate GSK3β activity in beta cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our preceding studies documented that glucose activated Akt through an autocrine/paracrine effect of insulin with subsequent activation of the PI3K pathway [26,28]. To extend these observations, we sought to test whether changes in glucose could regulate GSK3β activity in beta cells.…”
Section: Resultsmentioning
confidence: 99%
“…GLP-1 and GIP are glucoincretin hormones that are released from gut cells upon food intake and potentiate glucose activation of insulin secretion by b cells. A mechanistic explanation for Akt activation by insulin secretagogues would be an autocrine effect of secreted insulin through its binding to the insulin receptor (IR) at the surface of b cells (Ohsugi et al 2005). Consistently, in cultured cells, glucose regulates FOXO1 through the insulin signaling pathway (Martinez et al 2006).…”
Section: Foxo-linked Pathways In B Cellsmentioning
confidence: 95%
“…To understand the mechanism by which TNF-␣ treatment decreases GSIS, we have explored its impact on the insulin signaling pathway, since its activation is involved in glucose stimulus-secretion coupling (8,42). We have shown that the IRS-2/ Akt/AS160 pathway is involved in GSIS in primary beta cells (9), and a recent report indicates that an IGF-2/IGF-1 receptor autocrine loop underlies the glucose effect on insulin signaling mediated by IRS-2 (17).…”
Section: Discussionmentioning
confidence: 99%